2015
DOI: 10.7314/apjcp.2014.15.23.10281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and in vitro Anti-Tumoral Evaluation of Erlotinib-PCEC Nanoparticles

Abstract: Background: Development of a nanosized polymeric delivery system for erlotinib was the main objective of this research. Materials and Methods: Poly caprolactone-polyethylene glycol-polycaprolactone (PCEC) copolymers with different compositions were synthesized via ring opening polymerization. Formation of triblock copolymers was confirmed by HNMR as well as FT-IR. Erlotinib loaded nanoparticles were prepared by means of synthesized copolymers with solvent displacement method. Results: Physicochemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
(49 reference statements)
0
25
0
Order By: Relevance
“…It seems to be there is a mess about the previously published NMR data of Erlotinib and its HCl salt [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . There are several reasons for this confusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems to be there is a mess about the previously published NMR data of Erlotinib and its HCl salt [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . There are several reasons for this confusion.…”
Section: Resultsmentioning
confidence: 99%
“…Silver stabilize deuterated CDCl 3 causes to yellow coloured precipitate, probably the reason of the reaction between the Ag and acetylene group, that is why, it cannot be used. Highly different melting points and colors are reported in lit [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Actually pure Erlotinib sample must be white.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gefitinib and Erlotinib are two drugs used for the treatment of advanced NSCLC. The mode of action of these two drugs is based on their capability to inhibit the tyrosine kinase activity of EGFR by competing with ATP for the ATP-binding site (Barghi et al, 2014;Han et al, 2015;Hsieh et al 2015). Recently published study developed a nanosized polymeric delivery system for the drug "Erlotinib" (Barghi et al, 2014).…”
Section: 233 Overexpression Of Egfr Protein In Bruneian Lung Cancersmentioning
confidence: 99%
“…ETB loaded polymeric NPs in mice has shown improved efficacy and reduced toxicities associated with the drug (223). Another study revealed polymeric NPs improved antitumor efficacy of ETB in A549 human lung adenocarcinoma cells (224). Formulation of reverse micelles containing ETB showed improved in vitro efficacy of ETB in pancreatic cancer cells (225).…”
Section: Central Hypothesis and Specific Aimsmentioning
confidence: 99%